PENINGKATAN PEMAHAMAN MATERI MAJAS METAFORA MELALUI MODEL TGT DENGAN BANTUAN MEDIA KARTU DOMINO PADA SISWA KELAS IV DI IBNU SINA SCHOOL - Dira Kusuma Wardani; Arifin Maksum; Anggit Aruwiyantoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve grade IV students' understanding of metaphorical majas material through the application of the Teams Games Tournament (TGT) learning model combined with domino card media. This research is a Classroom Action Research (PTK) conducted in two cycles in class IV B Ibsi School, with a total of 21 students. Data were collected through observation, interviews, documentation, and written tests, which were analyzed qualitatively and quantitatively. The results showed a significant increase in students' understanding after the implementation of the action. The pretest average score of 69 increased to 89 in the first cycle posttest, and reached 95 in the second cycle posttest, with learning completeness reaching 100%. This finding shows that the TGT model with domino card media is effective in creating an active, fun learning atmosphere, and supports a deeper understanding of the concept of metaphorical majas.